Comparison of matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) systems for the identification of moulds in the routine microbiology laboratory. (July 2019) - Dupont, D.; Normand, A.-C.; Persat, F.; Hendrickx, M.; Piarroux, R.; Wallon, M.
Abstract: Objectives: The purpose of this study was to compare the efficiency of mould identification of two matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) systems – Vitek MS (VMS) and Microflex LT (MLT) – and the MSI application. Methods: Moulds were collected retrospectively and prospectively to display epidemiological diversity of a microbiology laboratory. All of them were identified via sequencing. Strains were then identified using the VMS v3.0, the MLT, and the MSI software applied on MLT spectra. Rates of correct identifications to the species, to the complex, and to the genus level were compared with the molecular reference standard. Results: A total of 102 isolates were collected. The rate of correct identification to the species level with the MLT was 42.2% (43/102) with a threshold of 1.7 (vs. 16.7% (17/102) with a threshold of 2.0, p < 0.05). The VMS performed better than the MLT with a threshold of 1.7 for species (49.0% (50/102), p 0.33) and complex level identifications (71.6% (73/102) vs. 54.9% (56/102), p < 0.05). However the highest performances were observed when the MLT spectra were analysed via the Mass Spectrometry Identification (MSI) software reaching 90.2% (92/102) of correct identification to the species, 92.2% (94/102) to the species complex and 94.1% (96/102) to the genus level. Conclusions: The VMS performed better than the MLT for mould identification. However, it remains of utmost importance to expand commercial databases, as performances of the MLT highly improved when using the MSI software and its extended database, reaching far above the VMS system. Thus the VMS could benefit from the use of this online tool.